Hexabromocyclododecane alters malachite green and lead(II) adsorption behaviors onto polystyrene microplastics: Interaction mechanism and competitive effect. (February 2021) - Lin, Lujian; Tang, Shuai; Wang, Xuesong; Sun, Xuan; Yu, Anqi
Abstract: The role of microplastics (MPs) as a carrier of pollutants in water environment is an emerging issue; however, information regarding the underlying mechanisms for malachite green (MG) and Pb(II) adsorption onto hexabromocyclododecane (HBCD)-polystyrene (PS) composites MPs (HBCD-PS MPs) is still lacking. In this study, the adsorption behaviors and mechanisms of MG and Pb(II) onto PS and HBCD-PS MPs were investigated in batch adsorption experiments. The amounts of MG and Pb(II) adsorbed onto PS MPs were negligible while the presence of HBCD significantly enhanced the adsorption of MG and Pb(II) onto HBCD-PS MPs. The results of intra-particle and film diffusion model confirmed that the adsorption of MG and Pb(II) onto HBCD-PS MPs was dominated by intra-particle diffusion. The maximum adsorption amount ( q m ) of Pb(II) and MG onto HBCD-PS MPs followed the sequence of Pb(II) (3.33 μmol g −1 ) > MG (1.87 μmol g −1 ). In binary systems, MG and Pb(II) showed competitive adsorption onto HBCD-PS MPs, and Pb(II) exhibited relatively higher affinity to be adsorbed onto HBCD-PS MPs. Solution pH and salinity played a crucial role in the adsorption process. XPS analysis suggested that the –Br participated in the adsorption process as an electron-withdrawing group. Overall, electrostatic interaction regulated the adsorption of MG and Pb(II) onto HBCD-PS MPs. Results from this study demonstrated that HBCD could enhance the role of MPs in the MG and Pb(II) migration by changing their adsorption behavior onto MPs. Graphical abstract: Image 1 Highlights: HBCD significantly enhanced the adsorption of MG and Pb(Ⅱ) onto HBCD-PS MPs. MG and Pb(Ⅱ) adsorption onto HBCD-PS MPs was dominated by electrostatic interaction. MG and Pb(II) showed competitive adsorption onto HBCD-PS MPs in binary systems. HBCD could enhance the role of MPs in the migration of cationic pollutants.